Action research in South African education : a critical praxis - Makoelle, Tsediso Michael (Sunpress, 2019)
"In an increasingly complex and challenging profession, the need for teachers, administrators and school systems to become involved in professional development activities is ever present. Action Research in South African Education: A Critical Praxis is a culmination of varying reflective accounts Professor Makoelle made as a teacher, an academic and a devoted action researcher. The book delves into his beliefs, attitudes and conceptions about the evolving discourse of Action Research in education and how it could be operationalised in varying educative contexts. The conversation fosters openness toward new ideas and learning new innovations, as well as giving teachers ownership of effective practices. It ultimately provides teachers with the necessary skills, knowledge, and focus to engage in meaningful inquiry about their professional practice."--Publisher's description